Pengaruh Pertumbuhan Ekonomi Terhadap Tingkat Pengangguran dan Kemiskinan di Kabupaten Sidoarjo. - Nur Hidayatillah; Rifdatul Hanifah; Tohonan Rohani Silaban; Riska Intan Praminingtyas; Dimas Alvario Darmaenda; Ravellino Dwi Cahya; Fendi Riyanto; Johanes Putra; Arga Christian Sitohang (Jurnal Mahasiswa Kreatif, 2024)
In a region, economic development is very important, especially to improve the economy and improve the welfare of the people. Economic development is a process of attempting to improve a nation's standard of living as measured by the level of real income per capita which involves major changes in social structure, community attitudes, eradicating poverty and reducing inequality (Rapanna and Sukarno, 2017). Economic development aims to equalize economic development and its results for the entire community, increase the rate of economic growth, expand employment opportunities, and minimize differences in regional capabilities. The success of a region's development can be seen from its economic growth. Where the higher regional economic growth can be a benchmark and indicator of the high level of development success and economic conditions of the region. If the economic growth of a region is lower, it indicates low development in that region and weak economic conditions (Ananda, 2017).